Drivers of year-to-year variation in exacerbation frequency of COPD: analysis of the AERIS cohort. Issue 1 (25th February 2019) - Wilkinson, Tom M.A.; Aris, Emmanuel; Bourne, Simon C.; Clarke, Stuart C.; Peeters, Mathieu; Pascal, Thierry G.; Taddei, Laura; Tuck, Andrew C.; Kim, Viktoriya L.; Ostridge, Kristoffer K.; Staples, Karl J.; Williams, Nicholas P.; et al.
The association between exacerbation aetiology and exacerbation frequency is poorly understood. We analysed 2-year follow-up data from a prospective observational study of patients with chronic obstructive pulmonary disease (COPD) (www.clinicaltrials.gov identifier number NCT01360398) to evaluate year-to-year variation in exacerbation frequency and related aetiology. A total of 127 patients underwent blood and sputum sampling monthly and at exacerbation to detect respiratory infections and eosinophilic inflammation; 103 continued into year 2 and 88 completed both years. The most common bacterial species at stable state and exacerbation was Haemophilus influenzae . Among infrequent exacerbators (one exacerbation per year), the incidence of viral infection at exacerbation was high (60.0% (95% CI 35.1–81.7%) in year 1 and 78.6% (53.4–94.2%) in year 2). Those with more frequent exacerbations tended to have higher relative incidence of bacterial than viral infection. Patients with at least two additional exacerbations in year 2 versus year 1 had a higher risk of H. influenzae colonisation at stable state than those with at least two fewer exacerbations, as detected by culture (OR 1.43 (95% CI 0.71–2.91) versus 0.63 (0.40–1.01), p=0.06) and PCR (1.76 (95% CI 0.88–3.51) versus 0.56 (0.37–0.86), p<0.01). This was not seen with other infection types or eosinophilic inflammation. Analysis of the same cohort over 2 years showed, for the first time, that changes in yearly COPD exacerbation rate may be associated with variations in H. influenzae colonisation. Analysis of the same cohort of patients over 2 years showed that changes in yearly COPD exacerbation rate may be associated with variations in Haemophilus influenzae colonisation http://ow.ly/Qe9430nkT7U